Bridging the integer gap: Computer-assisted instruction's effects on student achievement, gender equity, and learning perceptions - Dogbe, Saviour; Ali, Clement (International Journal of Didactic Mathematics in Distance Education, 2026)
Despite extensive research on Computer-Assisted Instruction (CAI) in mathematics education, few studies have specifically examined its effectiveness for teaching integer operations—a foundational yet persistently challenging topic for students. This study addressed this gap by examining the effects of CAI on students' achievement in integer operations and exploring potential gender differences in learning outcomes. A quasi-experimental pretest-posttest nonequivalent groups design was employed with 44 Year 2 students (22 experimental, 22 control) over four weeks. The experimental group received CAI-based instruction using interactive software with visual representations and immediate feedback, while the control group was taught using traditional methods. Data were collected using a Mathematics Achievement Test and a perception questionnaire, then analyzed using independent sample t-tests at p < 0.05. Results revealed that the experimental group achieved significantly higher post-test scores (M = 13.19, SD = 4.19) compared to the control group (M = 10.71, SD = 3.70), with t = 2.03, p = 0.049. Retention tests confirmed sustained learning gains four weeks post-intervention. No significant gender-based differences were found (p = 0.96), indicating CAI benefited male and female students equally. Student perceptions were overwhelmingly positive (M > 3.73), with participants appreciating CAI's interactive features, self-paced learning, and enhanced conceptual understanding. The study recommends integrating CAI into mathematics instruction to improve student engagement, understanding, and achievement in integer operations, particularly given its equitable benefits across gender groups.